2022
DOI: 10.1038/s41598-022-16409-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of fulvestrant long-term benefit in hormone receptor-positive/HER2 negative advanced breast cancer

Abstract: We retrospectively investigated in women treated with fulvestrant for HR+/HER2 negative advanced breast cancer clinical, pathological and molecular features associated with long-term benefit from treatment defined as being progression-free at 18 months. Specifically, we analyzed on formalin-fixed paraffin-embedded tumor samples ESR1 and PI3KCA mutations and miRNAs profiles. 59 patients were evaluable (median age of 67 years, range 32–92). 18-month PFS rate was 27%; the lack of visceral metastases significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Also, genes linked to the positive regulation of epithelial cell proliferation biological processes are related to the induction of metastasis and inhibition of breast cancer cell apoptosis through the promotion of epithelial cell proliferation via estrogen [44,45]. These results demonstrate the effectiveness of our computational method in unveiling important molecular mechanisms pertaining to breast cancer therapy) that have been approved for breast cancer treatment (see Figure 3) [61][62][63]. Both drugs identified two drug targets, PGR and ATP1A2.…”
Section: Dataset1mentioning
confidence: 61%
See 2 more Smart Citations
“…Also, genes linked to the positive regulation of epithelial cell proliferation biological processes are related to the induction of metastasis and inhibition of breast cancer cell apoptosis through the promotion of epithelial cell proliferation via estrogen [44,45]. These results demonstrate the effectiveness of our computational method in unveiling important molecular mechanisms pertaining to breast cancer therapy) that have been approved for breast cancer treatment (see Figure 3) [61][62][63]. Both drugs identified two drug targets, PGR and ATP1A2.…”
Section: Dataset1mentioning
confidence: 61%
“…Consequently, we encoded the dataset as a 736 × 119 matrix, including a column vector for drug responses, in which 256 BC patients achieved a complete response (CR) while 480 had a failed complete response (FCR). We had 11 treatments in which the 736 samples were distributed accordingly as follows: paclitaxel (169), paclitaxel + ABT 888 + carboplatin (63), paclitaxel + AMG-386 (110), paclitaxel + AMG-386 + trastuzumab (18), paclitaxel + MK-2206 (56), paclitaxel + MK-2206 + trastuzumab (31), paclitaxel + neratinib (105), paclitaxel + pembrolizumab (67), paclitaxel + pertuzumab + trastuzumab (43), paclitaxel + trastuzumab (25), and T-DM1 + pertuzumab (49). The gene expression data were performed using a reverse phase protein array (RPPA) microarray at George Mason University.…”
Section: Gse196093: Dataset3mentioning
confidence: 99%
See 1 more Smart Citation
“…RNA quality and quantity was measured with the High-Sensitivity RNA ScreenTape system (Agilent Technologies, Cernusco Sul Naviglio (Mi), Italy). Then, 50 ng of total RNA were used for miRNA profiling using the nCounter Human v3 miRNA Panel (NanoString Technologies, Seattle, WA, USA), as previously described [36]. The nCounter Flex instrument was used and all counts were gathered by scanning for 280 fields of view per sample.…”
Section: Mirna Analysesmentioning
confidence: 99%
“…Downregulation of ESR1 gene expression by miRNAs has been shown to be one mechanism of fulvestrant resistance. A recent study examining predictors of fulvestrant long-term benefits reported the ESR1 -targeting miR-520d-3p to be negatively associated with 18-month progression-free survival (PFS) [ 48 , 146 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%